Perencanaan Komunikasi Pemerintah Kota Kediri dalam Membangun Citra Walikota Perspektif Islam - Lukman Hakim; Yhova Hana Bunga Fadila (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
Communication planning is a very important thing in the smooth running of a program, especially in terms of branding. Public relations has the task of fostering good relations with the public, both internally and externally so as to create a positive image. Of course, these activities require careful communication planning in order to get maximum results. Therefore, this journal was written to find out the communication planning carried out by the Kediri City Government in Building the Image of the Mayor of Kediri. This research uses qualitative research, where the researcher conducts the observation and interview stages to be able to describe the research results based on the facts that researchers get in the field. The data was obtained from the interview process with the Head of the Protocol and Communication Section of the Kediri City Government. From the results of the interview, it was found that there are 2 elements of communication planning used in efforts to build the image of the Mayor of Kediri, namely internal and external elements. Internal means relating to the agency itself, while external means the public or society, which in its implementation utilizes 4 social media, namely Instagram, Facebook, Tik Tok, and Youtube.